Autonomous Energy Harvesting and Prevention of Cell Reversal in MFC Stacks. Issue 3 (1st January 2017) - Papaharalabos, George; Stinchcombe, Andrew; Horsfield, Ian; Melhuish, Chris; Greenman, John; Ieropoulos, Ioannis
Abstract : This study presents a novel method for avoiding cell reversal whilst optimising energy harvesting from stacked Microbial Fuel Cells (MFCs) by dynamically reconfiguring the electrical connections between them. The sequential changing of in-parallel and in-series electrical connections in an 8-MFC stack resulted in energy being transferred twice as fast into a super-capacitor avoiding cell reversal in MFCs as opposed to a fixed in-series configuration. This approach, allows for a lower internal resistance state within the stack compared to a fixed electrical configuration. This is critical in the initial stages of energy extraction from MFCs connected electrically in-series where the impedance of the capacitor is drawing high levels of current and cell reversals are likely to occur and hinder performance. Automation of electrical connections doubled the extracted power from the stack whilst halving the charging times without any cell reversal occurrence. The electrical reconfiguring of MFCs was performed by a USB-powered switch-box that modulated the stack's connections. This lead to the development of an energy autonomous switch-box circuitry powered solely by the MFC stack with negligible impact on the overall energy harvesting efficiency (i.e. above 90%).